An ion signal responsive dynamic protein nano-spring constructed by high ordered host–guest recognition. Issue 14 (29th January 2016) - Si, Chengye; Li, Jiaxi; Luo, Quan; Hou, Chunxi; Pan, Tiezheng; Li, Hongbin; Liu, Junqiu
Abstract : A Ca 2+ responsive protein self-assembly nano-spring was developed through host–guest interactions between cucurbit[8]uril and tripeptide FGG tags of fusion protein FGG-recoverin-GST. Abstract : A protein self-assembly nano-spring was developed through host–guest interactions between cucurbit[8]uril and tripeptide FGG tags of fusion protein FGG-recoverin-GST. Fine control of the conformational changes of the Ca 2+ -responsive domain allows for a 50% stretch of the protein nano-spring as it switches from the contracted state to the extended state.